Apakah Usia Berpengaruh? Perbedaan Individual Disaster Resilience antara Remaja dan Dewasa Penyintas Banjir di Kabupaten Bandung - Afifah Rufaidah; Maria Jane Tienoviani Simanjuntak (Universitas Mercu Buana, 2026)
This study was conducted due to the high risk of flooding in Bandung Regency, which requires individuals to develop disaster resilience. However, differences in developmental stages can influence the knowledge, attitudes, and behavioral responses of adolescents and adults toward flood disasters, which may lead to differences in individual disaster resilience. The study aims to identify differences in individual disaster resilience between adolescents and adults in coping with flooding in Bandung Regency. This study employed a quantitative approach, involving 439 respondents consisting of adolescents aged 10–21 years and adults aged 22–60 years, all residing in Bandung Regency and having experienced flooding. The instrument used was the Disaster Resilience Scale for Individuals (DRSi), which measures three dimensions: knowledge, readiness, and action. Data analysis was conducted using the Mann–Whitney U test. The results indicate a significant difference in individual disaster resilience between adolescents and adults (U = 40810, p < 0.001), with the adult group having a higher mean score (M = 25.16) compared to the adolescent group (M = 18.43). Significant differences were also found in the dimensions of knowledge, readiness, and action. Thus, adults demonstrate better understanding, preparedness, and action in coping with floods compared to adolescents.